The Influence of Human Resource Information System on Employee Performance Resonant Leadership Style as a Moderating Variable - Syuryatman Desri; Muhammad; Cuhenda; Yoana Amelia Dewi; Fitri Devi Lestari Izaak (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
With an explanatory approach, this quantitative research examines the influence of the human resource information system (HRIS) on employee performance and whether or not the resonant leadership style moderates this relationship. Primary data were collected from 350 Hypermart employees across Indonesia using a ten-item online questionnaire. Data were analyzed using Smart PLS 4.0. The results show that HRIS positively and significantly affects employee performance, with a p-value of 0.013. This implies that HRIS helps employees complete their tasks and achieve targets, enhancing performance. Additionally, the Resonant Leadership Style significantly moderates the influence of HRIS on performance, as indicated by a p-value of 0.004. Leaders with a resonant style can strengthen the effectiveness of HRIS, supporting better task completion and performance outcomes. These findings confirm the acceptance of both proposed hypotheses. The study highlights the importance of technological systems and leadership style in improving employee performance.